ANALISIS STRUKTUR KALIMAT DALAM BERITA DARING INDONESIA(KAJIAN SINTAKSIS) - Anggun Naja Yuliarti; Netti yuniarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze sentence types and syntactic function structures (S–P– O–K: Subject–Predicate–Object–Adverbial) in Indonesian online news texts published by Kompas, Detik, and CNN Indonesia in October 2025. This research employed a descriptive qualitative approach using documentation techniques. The data consisted of selected sentences taken purposively from online news articles covering economic, educational, social, and cultural topics. Data analysis was conducted through sentence identification, classification of sentence types (simplex, complex, and compound), analysis of syntactic functions, and interpretation based on Indonesian syntactic theories. The findings indicate that complex sentences are the most frequently used sentence type, particularly in Kompas and CNN Indonesia, as they allow journalists to present information in a more detailed and contextual manner through subordinate clauses. Meanwhile, Detik tends to use simplex sentences, reflecting its emphasis on brevity and speed in news delivery. Compound sentences appear less frequently across the three media outlets. In terms of syntactic structure, the dominant pattern found is S–P–O–K, with variations in the expansion of adverbial elements such as time, purpose, and context. Overall, the syntactic patterns found in online news texts demonstrate consistency with standard Indonesian grammatical rules and reflect the editorial styles and communicative strategies of each media outlet.